Influence of Chronic Stroke on Functional Arm Reaching: Quantifying Deficits in the Ipsilesional Upper Extremity - Subramaniam, Savitha (Rehabil Res Pract, 2019)
PURPOSE: The purpose of this study was to quantify ipsilesional upper extremity (UE) stand-reaching performance (kinematics and kinetics) among chronic stroke survivors. METHOD: Community-dwelling chronic stroke survivors (n=13) and age-similar healthy adults (n=13) performed flexion- and abduction-reaching tasks. Surface EMG and acceleration were sampled using wireless sensors from the prime movers (anterior and middle deltoid) and provided performance-outcome (reaction time, burst duration, movement time, and movement initiation time) and performance-production (peak acceleration) measures and were then evaluated. RESULTS: Individuals with chronic stroke demonstrated significantly reduced performance outcomes (i.e., longer reaction time, burst duration, movement time, and movement initiation time) and performance production ability (i.e., smaller peak acceleration) compared to their healthy counterparts (p < 0.05) for both flexion- and abduction-reaching movements. CONCLUSION: Our results are suggestive of post-stroke deficits in ipsilesional motor execution during a stand-reaching task. Based on these findings, it is essential to integrate ipsilesional UE training into rehabilitation interventions as this might aid functional reaching activities of daily living and could ultimately help community-dwelling chronic stroke survivors maintain their independent living.